Pretherapy Ferumoxytol-enhanced MRI to Predict Response to Liposomal Irinotecan in Metastatic Breast Cancer - Ravi, Harshan; Arias-Lorza, Andres M.; Costello, James R.; Han, Hyo Sook; Jeong, Daniel K.; Klinz, Stephan G.; Sachdev, Jasgit C.; Korn, Ronald L.; Raghunand, Natarajan (Radiology. Imaging cancer, 2023)
Purpose To investigate ferumoxytol (FMX)-enhanced MRI as a pretreatment predictor of response to liposomal irinotecan (nal-IRI) for thoracoabdominal and brain metastases in women with metastatic breast cancer (mBC). Materials and Methods In this phase 1 expansion trial (ClinicalTrials.gov identifier, NCT01770353; 27 participants), 49 thoracoabdominal (19 participants; mean age, 48 years ± 11 [SD]) and 19 brain (seven participants; mean age, 54 years ± 8) metastases were analyzed on MR images acquired before, 1-4 hours after, and 16-24 hours after FMX administration. In thoracoabdominal metastases, tumor transverse relaxation rate (R* ) was normalized to the mean R* in the spleen (rR* ), and the tumor histogram metric rR* , representing the average of rR* in voxels above the th percentile, was computed. In brain metastases, a novel compartmentation index was derived by applying the MRI signal equation to phantom-calibrated coregistered FMX-enhanced MRI brain scans acquired before, 1-4 hours after, and 16-24 hours after FMX administration. The fraction of voxels with an FMX compartmentation index greater than 1 was computed over the whole tumor (FCIGT1) and from voxels above the 90th percentile R* (FCIGT1 R* ). Results rR* computed from pretherapy MRI performed 16-24 hours after FMX administration, without reference to calibration phantoms, predicted response to nal-IRI in thoracoabdominal metastases (accuracy, 74%). rR* performance was robust to the inclusion of some peritumoral tissue within the tumor region of interest. FCIGT1 R* provided 79% accuracy on cross-validation in prediction of response in brain metastases. Conclusion This first in-human study focused on mBC suggests that FMX-enhanced MRI biologic markers can be useful for pretherapy prediction of response to nal-IRI in patients with mBC. MRI Contrast Agent, MRI, Breast, Head/Neck, Tumor Response, Experimental Investigations, Brain/Brain Stem Clinical trial registration no. NCT01770353 © RSNA, 2023 See also commentary by Daldrup-Link in this issue.